2015
DOI: 10.1016/j.jprocont.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Functional diagnosability and detectability of nonlinear models based on analytical redundancy relations

Abstract: International audienceThis paper introduces an original definition of diagnosability for nonlinear dynamical models called functional di-agnosability. Fault diagnosability characterizes the faults that can be discriminated using the available sensors in a system. The functional diagnosability definition proposed in this paper is based on analytical redundancy relations obtained from differential algebra tools. Contrary to classical definitions, the study of functional diagnosability highlights some of the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…They had already been used to estimate parameters (or faults) when no initial guess of their values were known [6] and for doing fault detection [7]. According to [9], ARRs can take the following form:…”
Section: B Analytical Redundancy Relations (Arrs)mentioning
confidence: 99%
“…They had already been used to estimate parameters (or faults) when no initial guess of their values were known [6] and for doing fault detection [7]. According to [9], ARRs can take the following form:…”
Section: B Analytical Redundancy Relations (Arrs)mentioning
confidence: 99%
“…Furthermore, the order of derivatives is so high that they are hardly suitable for fault detection. In [11], the authors propose to relax the constraints of [3] and to use ARRs involving one or more faults for studying diagnosability and detecting faults, the advantage being to easier the obtention of ARRs with derivatives of lower order. The obtention of such ARRs is based on the work of [4].…”
Section: A the Modelsmentioning
confidence: 99%
“…The obtention of such ARRs is based on the work of [4]. From these particular ARRs, the definition of functional diagnosability was proposed in [11]. The authors showed that if the model is identifiable with respect to the faults, then the residuals of these ARRs forming the functional signature have distinct trajectories.…”
Section: A the Modelsmentioning
confidence: 99%
See 2 more Smart Citations